EFEKTIVITAS BIOPESTISIDA EKSTRAK KULIT NANAS (Ananas comosus) DAN BIOCHAR DARI SERBUK GERGAJI SEBAGAI PENGENDALI HAMA PADA TANAMAN TERUNG UNGU (Solanum melongena) - Nasywa, Fatihah; Aulya, Nailul Rahmi; Wulaningsih, Ratna Dewi; Putri, Cindy Aprilla (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
This study aims to determine the effectiveness of biopesticides derived from pineapple peel extract (Ananas comosus) and sawdust biochar in controlling pests in eggplant (Solanum melongena). The research was conducted over 14 weeks at the Laboratorium Pengamatan Hama Penyakit dan Agens Hayati, UPT Pusat Pengembangan Benih dan Proteksi Tanaman, Cibubur, Jakarta Timur, using a factorial Completely Randomized Design (CRD) consisting of two factors: biopesticide concentration (0%, 25%, 50%, 75%) and biochar application (0 g and 500 g). Parameters observed included plant height, number of leaves, and the intensity of aphid (Aphis gossypii) infestation. The analysis results showed that the treatments of biopesticide, biochar, and their interaction did not significantly affect plant growth and pest resistance statistically. However, descriptively the combination of the two factors showed a positive trend on the vegetative growth of purple eggplant (Solanum melongena). These results indicate that organic waste such as pineapple peels and sawdust has potential as an environmentally friendly pest control agent.